Cooperative Silver‐ and Base‐Catalyzed Diastereoselective Cycloaddition of Nitrones with Methylene Isocyanides: Access to 2‐Imidazolinones. Issue 23 (14th May 2020) - Chen, Yan; Wu, Yijing; Shatskiy, Andrey; Kan, Yuhe; Kärkäs, Markus D.; Liu, Jian‐Quan; Wang, Xiang‐Shan
Abstract : A protocol involving cooperative silver‐ and base‐catalyzed diastereoselective cycloaddition of nitrones with isocyanides is described, providing access to a wide range of 2‐imidazolinone derivatives with various functional groups as single diastereomers. Varying the base and temperature of the reaction allowed selective access to both diastereomers of the product. A plausible reaction mechanism is proposed and supported by DFT calculations. Abstract : A protocol involving cooperative silver‐ and base‐catalyzed diastereoselective cycloaddition of nitrones with isocyanides is described, delivering several valuable 2‐imidazolinones derivatives as single diastereomers. A plausible reaction mechanism is rationalized by DFT calculations. DBU plays dual roles in the developed reaction, acting as both the base and ligand.